Structural insights into the polymorphism of bismuth(III) di-n-butyldithiocarbamate by X-ray diffraction, solid-state (13C/15N) CP-MAS NMR and DFT calculations. (17th June 2017) - Gowda, Vasantha; Sarma, Bipul; Laitinen, Risto S.; Larsson, Anna-Carin; Ivanov, Alexander V.; Iuga, Dinu; Lantto, Perttu; Antzutkin, Oleg N.
Graphical abstract: The structures of two interconvertible crystalline polymorphs of the bismuth(III) di- n -butyldithiocarbamate complex are resolved by a combination of solid-state NMR, single crystal XRD and DFT modelling. Abstract: Two crystalline polymorphs of a binuclear tris(di- n -butyldithiocarbamato)bismuth(III) complex, I and II, with an empirical formula of [BiS2 CN( n -C4 H9 )2 3 ] were synthesised and characterised by X-ray diffraction (XRD), solid-state NMR and density functional theory (DFT) calculations. At the supramolecular level, these mononuclear molecular units interact in pairs via secondary Bi⋯S bonds, yielding binuclear formations of [Bi2 S2 CN( n -C4 H9 )2 6 ]. The polymorph I ( P 1 ¯ ) contains two isomeric non-centrosymmetric binuclear molecules of [Bi2 S2 CN( n -C4 H9 )2 6 ], which are related to each other as conformers, therefore having four structurally inequivalent bismuth atoms and twelve inequivalent dithiocarbamate ligands. In contrast, the structurally simpler polymorph II ( P 2 1 / n ) exists as a single molecular form of the corresponding centrosymmetric binuclear formation, comprising two structurally equivalent bismuth atoms and three structurally different dithiocarbamate groups. The polymorphs I and II were found to be interconvertible by altering the solvent system during the recrystallisation process. Sun et al. (2012) has reported a crystalline form of the title compound which resembles, but is not identical with, polymorph II. Experimental solid-state 13 C and 15 N cross-polarisation (CP) magic-angle-spinning (MAS) NMR spectra of both polymorphs I and II were in accord with the direct structural data on these complexes. Assignments of the resonance lines in the solid-state 13 C and 15 N NMR spectra were assisted by chemical shift calculations of the crystals using periodic DFT.